The contribution of intersectionality to a public policy that responds to the needs of indigenous women - Alayza Sueiro, Adelaida (2021)
Intersectionality is a useful tool for the development of public policies that reach populations such as indigenous women because it helps to incorporate different dimensions of exclusion and discrimination that prevent populations from escaping vulnerability and poverty-related barriers. First, I explain the functioning of social categories and their role in the distribution of power and resources in order to understand the frameworks in which intersections become relevant; in addition, I analyze the approach of the State and its policies in structural situations that distribute power addressing or not the needs of indigenous women. In short, I seek to identify how much indigenous women's needs are incorporated —or not— in Peruvian Equal Opportunity Policy, depending on the approach it uses and how inclusive it is.